Academic stress and academic burnout in adolescents: a moderated mediating model - Gao, Xinhang (Frontiers in Psychology, 2023)
OBJECTIVE: To investigate the relationship and mechanisms of action among academic stress, academic anxiety, academic self-efficacy and academic burnout among adolescents. METHODS: A study of 929 Chinese adolescents (53.71% males, mean age = 11.94 years, SD = 0.77) was conducted using the Study Stress Questionnaire, Academic Anxiety Subscale, Junior Middle School Students' Learning Weariness Scale and the Academic Self-efficacy Questionnaire. RESULTS: ①Academic stress was significantly and positively correlated with academic anxiety and academic burnout, and significantly and negatively correlated with academic self-efficacy. ②Academic anxiety partially mediated the relationship between academic stress and academic burnout. ③Academic self-efficacy significantly moderated the direct effect of academic stress on academic burnout, and higher academic self-efficacy could buffer the negative effect of academic stress. ④Academic self-efficacy significantly moderated the second half of the mediated model's path (academic anxiety → academic burnout), that is, low academic self-efficacy amplified the risk effect of academic anxiety on academic burnout. CONCLUSION: Academic anxiety partially mediates the relationship between academic stress and academic burnout, and this mediating role is moderated by academic self-efficacy.